Impaired quality of life and functional status in patients with benign joint hypermobility syndrome. Issue 1 (3rd April 2015) - Sahin, Ebru; Gulbahar, Selmin; Baydar, Meltem; Ozcan Soylev, Gozde; Bircan, Cigdem; El, Ozlem; Kizil, Ramazan; Peker, Ozlen
Abstract: Objective : To evaluate the function and health-related quality of life [QoL], and to determine the relationship between pain, function and QoL in patients with benign joint hypermobility syndrome [BJHS]. Material and method : A total of 36 patients and 31 healthy controls were enrolled. Demographic characteristics were recorded and the patients were evaluated according to the Beighton score and Brighton criteria for BJHS. The assessment of pain was performed based on the visual analogue scale [VAS 0–10 cm]. Function and QoL were assessed using the Stanford Health Assessment Questionnaire [HAQ] and Nottingham Health Profile [NHP], respectively. Results : The mean age was 29.94 ± 6.04 years in the patient group and 30.16 ± 5.64 years in the control group. When the two groups were compared, there were significant differences in the HAQ scores. QoL was also significantly worse in the patient group in all dimensions of the NHP except for social isolation. There was a positive correlation between the Beighton score and the NHP-emotional reaction score . We have also observed a positive correlation between the HAQ scores and the pain [VAS], NHP-pain and NHP-Physical Mobility scores in the patient group. No correlation was observed among the other parameters. Conclusion : This study has demonstrated that function and QoL are significantly impaired in the patients with BJHS compared to healthy controls. Function and QoL as well as the pain should be assessed in the patients with BJHS. Also, the disease may not be benign as it is widely regarded.